PEMANFAATAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN KINERJA KEUANGAN PERUSAHAAN - Mahdianto Pandia (Universitas Methodist Indonesia, 2015)
This paper aims to determine how the use of information technology in improving the company's financial performance. Writing papers using literature review (library research). In relation to the financial performance of companies, information technology (IT) provides easiness in processing, managing and presenting financial information, with the support of an information system, so as to achieve a competitive advantage for the company and expected aorganisasi or aligned with business strategy. Accounting Information Systems (AIS), which is an information system can be said to be the oldest or an application is also the first major computer system to process accounting data